(untitled) - McKinney, Frank (New York, 2002)
If you wish to enter the real estate profession, you will find much in these pages to help you. However, anyone can benefit from these 49 philosophies and learn from the examples Frank describes. The stories of succeeding against enormous odds, sacrificing personal comfort to put everything into your business, living according to your vision, putting in a full day's work day in and day out, contributing to others, and enjoying your life every moment, I believe can provide great inspiration no matter what your stage or status in life. Rich De Vos, cofounder Amway, excerpted from the Foreword
Keywords: Success,Sự thành công; Psychological aspects,Khía cạnh tâm lý